Factors Associated with Cervical Cancer Screening in Women of Reproductive Age Using Via Method - Sihotang, Lydia; Kurniati, Mala; Yanti, Dhiny Easter; Anita, Anita; Muhani, Nova (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Cervical cancer is a malignant tumor that grows in the cervical area (cervix). In 2022, in South Lampung Regency, of the 11,077 women of reproductive age who underwent VIA screening, 19 (0.2%) tested positive. This study aimed to determine the factors associated with cervical cancer screening in Women of Reproductive Age (WRA) using the Visual Inspection with Acetic Acid (VIA) method. Quantitative research with a cross sectional approach, the sample of this study was 210 coupled female respondents aged 30-50 years who were of reproductive age. Bivariate analysis uses the chi square test and multivariate analysis uses logistic regression. There is a relationship between knowledge (p-value = 0.001, OR = 6.238), motivation (p-value = 0.001, OR = 7,667), the role of health workers (p-value = 0.007, QR = 4,091), and husband's support (p-value = 0.001, OR = 9,625) with cervical cancer screening using the VIA method. There is no significant relationship between the affordability of access to cervical cancer screening using the VIA method (p-value = 0,446, QR = 1,562). The husband's support variable is the dominant factor, with a p-value of 0.001 and an OR of 9,625. All variables influence women of reproductive age’s behavioral tendencies in cervical cancer screening, such as knowledge, motivation, the role of health workers, and husband's support (p value <0.05), except the affordability of access has no significant relationship. The influence of husband's support is the most dominant factor. Keywords: Cervical Cancer, VIA, and Women of Reproductive Age.